ESTUDO PRELIMINAR PARA A REMEDIAÇÃO DE ÁREAS RURAIS APÓS UM ACIDENTE NUCLEAR OU RADIOLÓGICO - Rochedo, Elaine R. R.; Silva, Diogo N. G.; de Luca, Christiano; Rochedo, Pedro R. R.; Wasserman, Maria Angélica Vergara; Perez, Daniel Vidal (Geochimica Brasiliensis, 2019)
The assessment of protective and remediation measures for rural areas is more complex than that for urban areas, due to the strong influence of large number of parameters and variables associated with climate, diet, eating habits, farming practices and the type of soil in the area. Thus, it is not possible to perform generic studies applicable to any kind of area. Specific studies and surveys should be made in the areas most likely to be contaminated due to a nuclear accident. Considering the Brazilian Nuclear Power Central, the prioritization of areas was based on radiological and economic aspects. This preliminary study demonstrated that the different soil types in Brazil are more relevant to the ingestion dose than the regional differences in the diets. The most relevant product for public dose was identified as the ingestion of milk. The contribution of milk to total ingestion dose depends on the season of the year when the accident occurs. The timing of the application of the measure has an important effect on the percentage dose reduction that can be achieved. In particular for I-131, protective measures related to milk ingestion must be considered within the emergency phase in order to be effective.